Recent trends in siRNA delivery for treatment of colorectal cancer: siRNA delivery for treatment of colorectal cancer - Momin, Taihaseen; Harugale, Satyajeet; Gulbake, Anamika Sahu; GULBAKE, ARVIND (International Journal of Applied Pharmaceutics, 2019)
Colorectal cancer (CRC) is the third most widespread cancer in the world. Currently, chemotherapy is effective treatment for CRC. Major problem with chemotherapy is the acquired multi drug resistance (MDR). Recently, siRNA (small interfering RNA) therapeutics has getting more attention to overcome the MDR in cancer and in various diseases. siRNA is a 21-23 base pair double stranded RNA having ability to silence specific genes at post transcriptional level. But, clinical practice of siRNA delivery having limitation due to enzymatic degradation by serum nucleases resulting poor stability, poor cellular uptake at target site. Now a days, development of various nanocarriers for efficient delivery of siRNA is a most challenging and rapidly growing research area. In this review, we summarize, the potential of various nanocarriers such as polymeric nanoparticles, lipid-based nanoparticles, inorganic nanoparticles, layered double hydroxide nanoparticles for siRNA delivery in colorectal cancer treatment.